DEVELOPMENT OF PRACTICAL DIETS FOR THE GROWTH AND SURVIVAL OF THE NILE TILAPIA (OREOCHROMIS NILOTICUS) - Basa, Gerard Amcil D.; Frio, Elena F. (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
In order to stabilize the price and supply of tilapia, improve the diet of tilapia, and save the livelihood of farmers across the nation, it is urgent to address the dependence on fish-based feed. The objective of this study is to create workable diets for Nile tilapia that reduce their reliance on fish-based products and find alternative sources of protein, while also fattening and enhancing growth development. This study aimed to answer the following questions, if the developed feed is effective in improving the growth of the Nile tilapia (Oreochromis niloticus) in terms of length and mass, which among the three treatments are the most effective in improving growth, and if there is a significant difference between treatments. To test the hypothesis that the feed developed from this study is effective in improving the growth of the Nile tilapia (Oreochromis niloticus) in terms of length and mass, an experiment was conducted, different treatments were made and applied to the tilapia, it is comprised of three treatments, treatment A with 66.7% (66.7g) golden apple snail, 10.65% (10.65g) Azolla (Azolla pinnata), 22.67% (22.67g) rice bran, treatment B with 66.6% (66.6g) golden apple snail, 10.3% (10.3g) kangkong (Ipomoea aquatica), 23.1% (23.1g)rice bran and treatment C fish feed (100g). The treatments were applied for 30 days. The results acquired were analyzed using one-way ANOVA in the SPSS software. The findings show that treatment B is the most effective treatment, but the three treatments have no significant difference in terms of mass and length.